2014
DOI: 10.6061/clinics/2014(11)10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vardenafil and pentoxifylline administration in an animal model of ischemic colitis

Abstract: OBJECTIVES:Vardenafil enhances dilatation of vascular smooth muscle and inhibits platelet aggregation. The purpose of this study was to evaluate the clinical effects of vardenafil and pentoxifylline administration in an experimental model of ischemic colitis.METHODS:Forty female Wistar albino rats weighing 250–300 g were randomized into five experimental groups (each with n = 8) as follows:1) a sham group subjected to a sham surgical procedure and administered only tap water; 2) a control group subjected to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, erythrocyte and plasma MDA levels were found to be more important in the control group compared to heparin and sham group. It is observed that this result [7,9,10,12,40] is consistent with the notifications of the researchers. The increase in MDA in the control group is caused by cleavage of lipid-containing structures such as plasma and cell membranes of oxygen radicals by the cells involved in the inflammatory response during the adventitious process [28,43].…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Atilgan et al [10] MDA levels were found to be higher and more important in the adhesion group than in the control group. In a study carried out by Azine et al [12], it is found that the difference in tissue MDA levels between sham and control groups was statistically significant. When comparing the control group with the pentoxifylline group, it was observed that the MDA level difference was significant.…”
Section: Discussionmentioning
confidence: 91%
“…This is probably because of the different mechanisms of action of these drugs. PTX enhances blood cell flexibility, including erythrocytes, favoring blood flow in peripheral vessels, 9,14,17,18 promotes platelet disaggregation, and increases fibrinolysis, contributing to reduced blood viscosity. 10,14,[18][19][20] Perhaps these effects require more time to begin to manifest.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Pentoxifylline (PTX) is a nonselective phosphodiesterase inhibitor, a methylxanthine derivative [10][11][12][13] whose molecular formula is C 13 H 18 N 4 O 3 , with a molecular weight of 278.31 Da. PTX is a drug with multiple pharmacologic properties, 14 promotes relaxation of vascular smooth muscle, causing vasodilatation and preventing vascular spasm, 15,16 enhances blood cell flexibility, including erythrocytes, favoring blood flow in peripheral vessels, 9,14,17,18 promotes platelet disaggregation, and increases fibrinolysis, contributing to reduced blood viscosity. 10,14,[18][19][20] PTX modulates the immunologic activity by acting on cytokines, suppresses leukocyte hyperactivity by reducing superoxide release and neutrophil adhesion, 17 inhibits the action of integrin and interleukin 2 (IL-2), preventing lymphocyte adhesion to endothelial cells, 21 and reduces the synthesis of IL-1 and tumor necrosis factor a.…”
Section: Introductionmentioning
confidence: 99%
“…Pentoxifylline (PTX) is a phosphodiesterase inhibitor which has anti-inflammatory properties [ 7 ]. PTX and its metabolites increase the blood fluidity by reducing blood viscosity, inhibiting microvascular construction and blocking erythrocyte [ 8 ]. PTX regulated the inflammatory response with the decreased cellular activation, phagocytosis and endothelium adhesion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%